A Pyrene-4,5,9,10-Tetraone-Based Covalent Organic Framework Delivers High Specific Capacity as a Li-Ion Positive Electrode - Gao, Hui; Neale, Alex R.; Zhu, Qiang; Bahri, Mounib; Wang, Xue; Yang, Haofan; Xu, Yongjie; Clowes, Rob; Browning, Nigel D.; Little, Marc A.; Hardwick, Laurence J.; Cooper, Andrew I. (Journal of the American Chemical Society, 2022)
Electrochemically active covalent organic frameworks (COFs) are promising electrode materials for Li-ion batteries. However, improving the specific capacities of COF-based electrodes requires materials with increased conductivity and a higher concentration of redox-active groups. Here, we designed a series of pyrene-4,5,9,10-tetraone COF (PT-COF) and carbon nanotube (CNT) composites (denoted as PT-COFX, where X = 10, 30, and 50 wt % of CNT) to address these challenges. Among the composites, PT-COF50 achieved a capacity of up to 280 mAh g–1 as normalized to the active COF material at a current density of 200 mA g–1, which is the highest capacity reported for a COF-based composite cathode electrode to date. Furthermore, PT-COF50 exhibited excellent rate performance, delivering a capacity of 229 mAh g–1 at 5000 mA g–1 (18.5C). Using operando Raman microscopy the reversible transformation of the redox-active carbonyl groups of PT-COF was determined, which rationalizes an overall 4 e–/4 Li+ redox process per pyrene-4,5,9,10-tetraone unit, accounting for its superior performance as a Li-ion battery electrode.